Race v. suffrage: The determinants of development in Mississippi - Graziella Bertocchi; Arcangelo Dimico (Institute for the Study of Labor (IZA), 2011)
We investigate the long term determinants of political and economic outcomes over a new data set composed of Mississippi counties. We analyze the effect of disfranchisement on voting registration at the end of the nineteenth century (1896-9), as well as the impact of voting registration on education outcomes at different points in time, namely in 1917 and in the 1950s. Finally, we turn to the determinants of a broad array of development indicators for the year 1960 and for the 1960-2000 period. Our main conclusion is that race, rather than political institutions and education policies, is the main force driving the above outcomes.
urn:nbn:de:101:1-201110263558
Keywords: E25; H52; J15; N31; O11; P16; 330; race; institutions; development; inequality; education; Wahlrecht; Soziale Ungleichheit; Ethnische Gruppe; Bildungsverhalten; Entwicklung; Geschichte; USA (Südstaaten)